2008
DOI: 10.1152/ajplung.90351.2008
|View full text |Cite
|
Sign up to set email alerts
|

CRTH2 antagonism significantly ameliorates airway hyperreactivity and downregulates inflammation-induced genes in a mouse model of airway inflammation

Abstract: Prostaglandin D(2), the ligand for the G protein-coupled receptors DP1 and CRTH2, has been implicated in the pathogenesis of the allergic response in diseases such as asthma, rhinitis, and atopic dermatitis. This prostanoid also fulfills a number of physiological, anti-inflammatory roles through its receptor DP1. We investigated the role of PGD(2) and CRTH2 in allergic pulmonary inflammation by using a highly potent and specific antagonist of CRTH2. Administration of this antagonist ameliorated inflammation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 34 publications
8
46
0
Order By: Relevance
“…Our data on mucus hypersecretion are consistent with previous findings with the dual DP2/TP antagonist ramatroban (Uller et al, 2007) and selective DP2 antagonists (Uller et al, 2007;Lukacs et al, 2008) in murine allergic settings. Although outside the scope of this manuscript, a possible mechanism by which DP2 antagonists affect mucus production may be via direct action on neutrophils to reduce elastase and other proteases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data on mucus hypersecretion are consistent with previous findings with the dual DP2/TP antagonist ramatroban (Uller et al, 2007) and selective DP2 antagonists (Uller et al, 2007;Lukacs et al, 2008) in murine allergic settings. Although outside the scope of this manuscript, a possible mechanism by which DP2 antagonists affect mucus production may be via direct action on neutrophils to reduce elastase and other proteases.…”
Section: Discussionsupporting
confidence: 91%
“…Elevations of IL-6 and transforming growth factor-␤ have been demonstrated in murine smoke models of COPD (Obot et al, 2004;Churg et al, 2006). The effect of DP2 antagonism on IL-17 confirms the modest reduction in IL-17 gene expression that Lukacs et al (2008) observed in lungs from DP2 antagonisttreated mice relative to those from antigen-treated mice. IL-17 is implicated in promoting and sustaining neutrophilic inflammation; thus, the inhibitory effects of DP2 antagonism on pulmonary neutrophilia may, in part, be due to the reduction in basal lung IL-17 concentrations.…”
Section: Discussionmentioning
confidence: 55%
“…Due to its specificity, we believe this compound is a useful tool to analyze the biology of CRTH2 in animal models of inflammation. Consistent with the role of CRTH2 in promoting allergic inflammation at barrier surface of the skin and lung [14,25,26], CRTH2 inhibitor suppressed the oxazolone-induced contact dermatitis when administered orally or topically by modulating the expression of not only the Th2 cytokine IL13 but also other pro-inflammatory cytokines including IFNγ, IL-17 A and IL-21. More importantly, Compound A also reduced the severity of DSS-induced colitis as revealed by improved percentage body weight change, inflammatory biomarker, serum haptoglobin as well as histopathology and cytokine gene/protein expression.…”
Section: Discussionsupporting
confidence: 55%
“…The effects of Ramatroban on eosinophil recruitment are unlikely to be mediated by TP antagonism as eosinophils do not express TP and selective TP antagonists do not influence eosinophil function [16,28]. In recent studies with highly CRTH2 selective inhibitors, Boehme et al and Lukacs et al demonstrated that blocking the CRTH2 effectively prevented allergen induced skin inflammation and airway hyper-responsiveness [25,26]. As expected, they found that CRTH2 blockade remarkably reduced antigen specific serum IgE, IgG1 and IgG2a, and Th2 cytokines IL-13, IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies also demonstrated that activation of CRTH2 suppresses Th2 cell apoptosis (15), a process that is likely to impede the resolution of allergic inflammation. Allergic responses mediated by IgE, mast cells, Th2 cells, and eosinophils are dramatically reduced in mice in which CRTH2 is genetically ablated or by small molecule CRTH2 antagonists (16)(17)(18)(19)). Antagonism of CRTH2 is currently being considered as a potentially useful approach for the treatment of allergic diseases, including asthma, rhinitis, and atopic dermatitis (20).…”
mentioning
confidence: 99%